2002
DOI: 10.1016/s0928-8244(02)00378-4
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma gallisepticum: influence of cell invasiveness on the outcome of experimental infection in chickens

Abstract: Recently we have shown that a low (R(low)) and a high laboratory passage (R(high)) of the poultry pathogen Mycoplasma gallisepticum prototype strain R differ markedly in their capability to invade non-phagocytic eukaryotic cells. In the present study the infection traits of these two mycoplasma passages were compared in an in vivo setting. After aerosol inoculation of chickens, M. gallisepticum was re-isolated from the inner organs of birds infected with R(low), whereas no mycoplasma was recovered from the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…In view of the prevailing scenario, we tried to investigate whether M. agalactiae has the capacity to enter, survive and exit the eukaryotic host cells in a viable state, as this could explain the chronic, persistent and difficult-to-eradicate nature of its infections in spite of long antibiotic therapies. This phenomenon may also allow it to reach more favorable host niches by crossing the epithelial barrier as cell invasion is often considered a major factor for systemic spread ( Cieri et al, 2002; Much et al, 2002 ). Here, we provide evidence for the first time that M. agalactiae is able to invade eukaryotic host cells whereby quantitative results are supported by the qualitative double immunofluorescence assay.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the prevailing scenario, we tried to investigate whether M. agalactiae has the capacity to enter, survive and exit the eukaryotic host cells in a viable state, as this could explain the chronic, persistent and difficult-to-eradicate nature of its infections in spite of long antibiotic therapies. This phenomenon may also allow it to reach more favorable host niches by crossing the epithelial barrier as cell invasion is often considered a major factor for systemic spread ( Cieri et al, 2002; Much et al, 2002 ). Here, we provide evidence for the first time that M. agalactiae is able to invade eukaryotic host cells whereby quantitative results are supported by the qualitative double immunofluorescence assay.…”
Section: Introductionmentioning
confidence: 99%
“…This pathogen is known to invade, survive and multiply inside a variety of non-phagocytic cells such as chicken RBCs, HeLa cells, and chicken fibroblasts, [4] [9] . In addition, M. gallisepticum is known to colonize many extra-pulmonary tissues including blood, heart, spleen, liver and brain [4] , [5] , [7] , [8] , [10] . Indikova et al (2013) suggested that invasion may occur at the air sac, where the mucosal barrier is quite thin [7] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is now accumulating evidence that some mycoplasmas can invade non-phagocytic cells, and M. gallisepticum appears to be one such organism (Winner et al, 2000). The invasiveness of the strain of M. gallisepticum was reported to influence the outcome of experimental infections in chickens (Much et al, 2002) and a more invasive strain was found in the heart, brain, liver and kidney of infected birds, indicating haematogenous spread. The authors speculated that expression of the gapA gene might be a crucial factor in influencing cell invasion, because a highly passaged, avirulent derivative of the invasive strain had an irreversible mutation in this gene, which prohibited expression.…”
Section: Invasionmentioning
confidence: 99%